Comparison of the pervaporation separation of a water-acetonitrile mixture with zeolite-filled sodium alginate and poly(vinyl alcohol)-polyaniline semi-interpenetrating polymer network membranes - Naidu, B. V. K.; Bhat, S. D.; Sairam, M.; Wali, A. C.; Sawant, D. P.; Halligudi, Shivaraj B.; Mallikarjuna, N. N.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2005)
The pervaporation (PV) separation performance of ZSM-5- and Na-Y-type zeolite-filled sodium alginate (NaAlg) membranes were compared with those of pure NaAlg and semi-interpenetrating polymer network (semi-IPN) membranes of poly(vinyl alcohol) (PVA) with polyaniline (PANI) for the dehydration of acetonitrile. The PV separation characteristics of the zeolite-filled membranes showed a dependence on the nature of the zeolites. The variation of the acidity function of the ZSM-5 zeolite had an influence on the flux and selectivity of the membranes when compared to unfilled membranes. The crosslinked membranes were characterized by differential scanning calorimetry, X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy. Increasing the PANI content of the semi-IPN network increased the separation selectivity. Among the NaAlg membranes, the plain NaAlg membrane showed the highest selectivity of 414 at 30 mass % water in the feed mixture, whereas the Na-Y- and ZSM-5 (40)-filled NaAlg membranes exhibited much lower values of selectivity, that is, 7.3 and 4.3, respectively for 30 mass % water in the feed. When the flux and selectivity data of ZSM-5 (250)-filled NaAlg membranes were compared with that of Na-Y- or ZSM-5 (40)-filled NaAlg membranes, a noticeable increase in the selectivity for the ZSM-5 (250)filled NaAlg membrane was observed, but a somewhat comparable flux was observed compared to the plain NaAlg membrane. For the first time, PANI was polymerized with PVA to yield a semi-IPN. The total flux and water flux increased systematically, whereas the selectivity decreased greatly from 251.87 to 5.95 with increasing amounts of water in the feed. (c) 2005 Wiley Periodicals, Inc.
Keywords: Diffusion; interpenetrating network (IPN); zeolites

Chemoselective anti-Markovnikov hydroamination of alpha,beta-ethylenic compounds with amines using montmorillonite clay - Joseph, Trissa; Shanbhag, G. V.; Sawant, D. P.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A-Chemical, 2006)
The catalytic activity of montmorillonite clays as a catalyst for the hydroamination of alpha,beta-ethylenic compounds with amines was tested. Aniline and substituted amines reacted with alpha,beta-ethylenic compounds in the presence of catalytic amount of commercially available clay to afford exclusively anti-Markovnikov adduct in excellent yields. Aniline reacted with ethyl acrylate to yield only anti-Markovnikov adduct N-[2-(ethoxycarbonyl)ethyl] aniline (mono-addition product). No Markovnikov adduct (N-[1-(ethoxycarbonyl)ethyl]aniline and double addition product N,N-bis[2-(ethoxycarbonyl)ethyl]aniline were formed under selected reaction conditions. For a better exploitation of the catalytic activity in terms of increased activity and improved selectivity for the mono-addition product, the reaction parameters were optimized in terms of temperature, solvent, reactant mole ratio. Under optimized reaction conditions, montmorillonite clay K-10 showed a superior catalytic performance in the hydroamination of ethyl acrylate with aniline with a conversion of aniline to mono-addition product (almost 100% chemoselectivity) with a high rate constant 0.3414 min(-1) compared to the reported protocols. The dependence of conversion of aniline over different types of montmorillonite clays (K-10, K-20, K-30, Al-Pillared clay and untreated clay) has also been discussed. The activities of clay for the hydroamination of different aromatic and aliphatic amines have also been investigated. Under harsh reaction conditions (increased temperature and long reaction time) small amounts of di-addition products were observed. The kinetics data has been interpreted using the initial rate approach model. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: alpha; amines; anti-Markovnikov addition product; beta-ethylenic compounds; chemo-selective; hydroamination; K-10 montmorillonite clay